Cycloaddition reactions of 3-aryl-5-phenyl-5H,7H-thiazolo[3,4-c]oxazol-4-ium-1-olates - Melo, Teresa M. V. D. Pinho e (2002)
Intermolecular 1,3-dipolar cycloaddition of (5R)- and (5S)-3,5-diphenyl-5H,7H-thiazolo[3,4-c]oxazol-4-ium-1-olates, (5R)- and (5S)-3-(p-methoxyphenyl)-5-phenyl-5H,7H-thiazolo-[3,4-c]oxazol-4-ium-1-olates with a range of dipolarophiles is described. New chiral 5-aryl-3-phenyl-1H,3H-pyrrolo[1,2-c]thiazoles with R and S configuration were obtained. The structure of methyl (3R)-3-phenyl-5-(p-methoxyphenyl)-1H,3H-pyrrolo[1,2-c]thiazole-6-carboxylate was determined by X-ray crystallography. The synthesis of 7,7a-dihydro-1H,3H-pyrrolo[1,2-c]thiazole-6,7-dicarboxylates was also achieved.